Online counselling services: university students’ perception - Abu Shahim, M. R.; Shaudi, L. S.; Zainudin, Z. N.; Kamarul, M. S. (Karadeniz Technical University, 2021)
Online counselling is no longer something new. It offers faster, safer and more practical in getting counselling services. This study aims to examine the perceptions of university students toward online counselling services which include aspects of attitude, knowledge and readiness at Universiti Malaysia Terengganu. This quantitative study has a total of 263 respondents from two different studies; social sciences and technology sciences. The Perceptions Toward Online Counseling Questionnaire is used as the instrument. The collected data were analysed using quantitative method. The data obtained were analysed with the help of Statistical Package for Social Science (SPSS) 23.0 for Windows. t-test analysis was used to analyse the data. The results showed that there was no significant difference in perceptions of attitude and readiness toward online counselling services based on the field of study. However, there is a significant difference in the perception of knowledge toward online counselling services based on the field of study. Therefore, the implications and recommendations for future research also discussed.